Modeling deformation of corroded buried steel pipes and design of protective measure - Wordu, Alvan H.; Tee, Kong Fah; Shafiee, Mahmood (ASME, 2019)
Corrosion damage is reported to be one of the leading causes of steel pipeline failure causing significant financial losses to operators and damage to the surrounding environment. As part of a rising confrontation to pipeline integrity management, researchers are continuously seeking better ways to assist on how to identify, assess and prevent such incidents. Thus, there is a crucial need to establish a connection between assessment of pipeline condition and its structural stability. To achieve this, a 3-dimensional FE model is developed. The effects of geometry parameters such as defect thickness and spread angle are considered. Results show that thicker pipelines with corrosion groove performed better structurally than slender equivalents. The impact of corrosion damage is assessed to be significant on pipe stability with pipelines experiencing higher displacement when the damage angle becomes greater than 30 degrees. Lastly, a protective measure is designed for preventing excessive deflection of damaged pipes.
Keywords: Corrosion; Buried Steel Pipelines; Deflection; Finite Element Modelling; Pipe Wall Thickness